Creative manipulation: a case study of confirmshaming as a deceptive design pattern - Knyzelis, Milvydas (Creativity Studies, 2024)
This research article explores the intersection between creativity and deceptive design patterns, focusing on the concept of confirmshaming within the broader framework of a creative society. Focusing on confirmshaming as a case study, this article explores how such deceptive design practices exemplify the dark side of creativity, where digital technologies are used to manipulate user behavior. The aim of this research is to explore the mechanisms and impacts of confirmshaming on user decision-making. By emphasizing the importance of ethical awareness and accountability in digital design practices, this study advocates for the preservation of user autonomy in digital interactions. Ultimately, this article should serve as a call to action for the design community to prioritize responsible and humane design of digital technology.